Sodium-ion battery positive electrode material capable of stably circulating under high voltage and preparation method of sodium-ion battery positive electrode material
By using P2/O3 biphase structure and doping of Li, Ni, Cu and Fe elements in the positive electrode material of sodium ion battery, the problem of poor cycling stability at high voltage is solved, and high specific capacity and excellent cycling performance are achieved. It is at a high voltage of 2.0-4.5V, the material exhibits a capacity retention rate of 98.6%.
Patent Information
- Application Number
- CN202411242957.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-05
- Publication Date
- 2025-01-14
AI Technical Summary
The existing sodium ion battery positive electrode materials have poor cycling stability at high voltages, making it difficult to achieve high specific capacity and excellent cycling performance at the same time.
The layered oxide positive electrode material with P2/O3 biphase structure is adopted. Through multi-element doping of Li, Ni, Cu, and Fe, the lattice distortion and element mixing during the charge and discharge process are suppressed. The preparation method includes sodium, copper, The oxides of iron, nickel, manganese and lithium are mixed and wet ball milled and sintered to form a material of Na0.7Li0.03][CuxFeyNizMn0.92-x-y-zLi0.05]O2.
At high voltages of 2.0-4.5V or even 2.0-4.7V, the material exhibits excellent discharge specific capacity and cycle stability. The capacity retention rate after 100 cycles reaches 98.6%, and has both high specific capacity and excellent rate performance. .
Smart Images

Figure CN119315024A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sodium ion batteries, and in particular relates to a positive electrode material for a sodium ion battery with stable circulation under high voltage and a preparation method thereof. Background Art
[0002] In order to reduce carbon emissions, it is essential to transform the fossil fuel economy into a renewable energy economy. Among all types of energy storage systems, rechargeable batteries have become a competitive choice due to their inherent characteristics of high energy efficiency, long cycle life and minimal maintenance. With similar electrochemical principles, sodium-ion batteries are considered to be the most promising supplement to lithium-ion batteries (LIBs) due to the abundance of sodium and its low cost compared to lithium. In the past decade, various sodium-ion battery cathode materials have been proposed, such as layered oxides, polyanionic compounds and Prussian blue analogs. Compared with other cathode materials, transition metal layered oxide cathode materials have become a promising class of sodium-ion battery cathode materials due to their abundant active element centers, tunable composition and good electrochemical activity.
[0003] As we all know, within the safe working range of the electrolyte, the higher the discharge voltage of the positive electrode material, the greater the energy density of the battery. Increasing the working voltage of the positive electrode material is an effective way to improve the energy density of the battery. This has also attracted more and more researchers to turn their attention to the research on high-voltage sodium-ion battery positive electrode materials. However, when the working voltage of the layered oxide positive electrode material exceeds 4.0V, the positive electrode material is prone to complex structural phase changes and structural damage, resulting in poor cycle stability of the material under high voltage. Especially for the relatively high capacity O3 layered oxide positive electrode material, when charged to a high voltage, structures such as O"3 and O1 will be produced. This phase change has poor reversibility and is accompanied by a large volume change, resulting in poor cycle performance of the material. Therefore, it is difficult for O3 type materials to achieve both high capacity and excellent cycle performance. For example, in the article "Study on the Reversible Electrode Reaction of Na 1- x Ni 0.5 Mn 0.5 O2 for a Rechargeable Sodium-Ion Battery" reported O3-type NaNi 0.5 Mn 0.5O2 material shows a high specific capacity of 185mA h / g in the voltage range of 2.2-4.5V and 0.1C rate conditions, but the specific capacity is almost zero after 30 cycles. Generally, it is necessary to limit the battery's charge cutoff voltage (controlled to below 4V) to avoid the material from undergoing a large phase change with a large volume change at high voltage, thereby ensuring the material's cycle stability. However, limiting the battery's charge cutoff voltage usually comes at the expense of specific capacity. For example, in an article published by Shinichi Komaba, when the charge and discharge voltage is limited to 2.2-3.8V, NaNi 0.5 Mn 0.5 O2 showed a specific capacity of 125mA h / g, and the capacity retention rate was still 75% after 50 cycles, and the cycle performance was significantly improved. In addition, doping with a variety of active and inactive elements is also an important way to improve the cycle stability of layered oxide cathode materials, but the inactive elements usually introduced will lead to a decrease in the specific capacity of the material. For example, in the article "High-entropy substitution: A strategy for advanced sodium-ion cathodes with high structural stability and superior mechanical properties" published by Du Xinyu et al., they 0.5 Mn 0.5 Based on O2, NaNi was obtained by doping Co, Cu, Fe, Li, Ti, and Sn in the transition metal layer. 0.1 Mn 0.15 Co 0.2 Cu 0.1 Fe 0.1 Li 0.1 Ti 0.15 Sn 0.1 O2, after 100 cycles at a current density of 160 mA / g, the capacity retention rate of this material is 82.7%, but due to excessive doping with inert elements, its specific capacity is only 115 mA h / g at a voltage of 2-4.1 V. Limited by the unstable phase transition of layered oxide positive electrode materials under high voltage and the accompanying large volume change, it is difficult to achieve excellent cycle performance and high specific capacity at the same time.
[0004] Therefore, it is of great significance to develop cathode materials for sodium-ion batteries with high specific capacity and high cycle stability at high voltage. Summary of the invention
[0005] In view of the deficiencies in the prior art, the object of the present invention is to provide a sodium ion battery positive electrode material, wherein the sodium ion battery positive electrode material is a layered oxide positive electrode material with a P2 / O3 dual-phase structure.
[0006] Another object of the present invention is to provide a method for preparing the above-mentioned sodium ion battery positive electrode material.
[0007] Another object of the present invention is to provide a sodium ion battery.
[0008] The purpose of the present invention is achieved through the following technical solutions.
[0009] A sodium ion battery positive electrode material, the general structural formula of which is [Na 0.7 Li 0.03 ][Cu x Fe y Ni z Mn 0.92-x-y-z Li 0.05 ]O2, where 0.1≤x≤0.4, 0.1≤y≤0.3, 0.1≤z≤0.3, 0.1≤0.92-xyz≤0.6.
[0010] Preferably, 0.1≤x≤0.2, 0.1≤y≤0.14, 0.1≤z≤0.3, 0.3≤0.92-xyz≤0.6.
[0011] Most preferably, x=0.2, y=0.1, z=0.1.
[0012] The method for preparing the above-mentioned sodium ion battery positive electrode material comprises the following steps:
[0013] S1, mixing a sodium source, a copper source, an iron source, a manganese source, a nickel source and a lithium source uniformly to obtain a precursor powder, wherein the ratio of sodium in the sodium source, copper in the copper source, iron in the iron source, nickel in the nickel source, manganese in the manganese source and lithium in the lithium source is 0.735:x:y:z:(0.92-xyz):0.084 in terms of molar fractions;
[0014] In S1, the sodium source is one or a mixture of sodium carbonate, sodium bicarbonate, sodium nitrate, sodium acetate and sodium oxalate.
[0015] In S1, the copper source is one or a mixture of copper oxide, copper chloride, copper nitrate, copper sulfate, copper carbonate, copper acetate and copper oxalate.
[0016] In S1, the iron source is one or a mixture of iron oxide, iron chloride, iron nitrate, iron sulfate, iron carbonate, iron acetate and iron oxalate.
[0017] In S1, the manganese source is one or a mixture of manganese oxide, manganese chloride, manganese nitrate, manganese sulfate, manganese carbonate, manganese acetate and manganese oxalate.
[0018] In S1, the nickel source is one or a mixture of nickel oxide, nickel chloride, nickel nitrate, nickel sulfate, nickel carbonate, nickel acetate and nickel oxalate.
[0019] In S1, the lithium source is one or a mixture of lithium oxide, lithium chloride, lithium nitrate, lithium sulfate, lithium carbonate, lithium acetate and lithium oxalate.
[0020] In S1, a sodium source, a copper source, an iron source, a manganese source, a nickel source and a lithium source are mixed and wet-ball-milled to be uniform.
[0021] In the above technical solution, the rotation speed of the wet ball mill is 300 to 1400 rpm, and the time of the wet ball mill is 0.5 to 3 hours.
[0022] In the above technical solution, acetone is used as a wet grinding dispersant in the wet ball milling, and the ball mill jar is made of alumina or zirconium oxide.
[0023] S2, sintering the precursor powder at 500-950° C. for 10-15 hours to obtain a positive electrode material for a sodium ion battery.
[0024] In S2, the heating rate to 500-950°C is 3-5°C / min.
[0025] In S2, sintering is preferably performed at 800-950°C for 10-15h.
[0026] A sodium ion battery comprises: a positive electrode, a negative electrode and a separator, wherein the positive electrode material in the positive electrode is the positive electrode material of the sodium ion battery.
[0027] In the above technical solution, the cycle stability of the sodium ion battery after 100 cycles at a high voltage of 2-4.5V and a current density of 1C is 98.6%.
[0028] In the above technical solution, the cycle stability of the sodium ion battery after 100 cycles at a high voltage of 2-4.7V and a current density of 1C is 89%.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] 1. The sodium ion battery positive electrode material of the present invention presents a P2 / O3 dual-phase crystal structure. Through the joint action of Li, Ni, Cu, and Fe, the lattice distortion and element mixing during the charge and discharge process are effectively suppressed. In particular, under high charging voltage, the sodium ion battery has excellent discharge specific capacity and cycle stability. When working at a high voltage of 2.0-4.5V or even 2.0-4.7V, it can still have high specific capacity, excellent cycle stability and excellent rate performance.
[0031] 2. The sodium ion battery positive electrode material of the present invention has the characteristic of low cost compared with high-nickel and cobalt-containing materials, provides a new solution for improving the cycle stability of sodium ion batteries under high voltage, and solves the technical problem of poor cycle stability of layered oxide positive electrode materials under high voltage. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is the XRD pattern of the sodium ion battery positive electrode material prepared in Example 1;
[0033] Figure 2 This is a SEM image of the sodium ion battery positive electrode material prepared in Example 1;
[0034] Figure 3 The sodium ion battery positive electrode material prepared in Example 1 7 Li ss-NMR test results;
[0035] Figure 4 The charge and discharge curve of the sodium ion battery prepared in Example 5 at a voltage range of 2-4.7V and a current density of 0.2C;
[0036] Figure 5 The charge and discharge curve of the sodium ion battery prepared in Example 5 at a voltage range of 2-4.5V and a current density of 0.2C;
[0037] Figure 6 This is a cycle performance diagram of the sodium ion battery prepared in Example 5 at a current density of 1C;
[0038] Figure 7 This is a cycle performance diagram of the sodium ion battery prepared in Example 5 at a current density of 2C;
[0039] FIG8( a ) is a graph showing different rate performances of the sodium ion battery prepared in Example 5 in the voltage range of 2-4.5 V, and FIG8( b ) is a graph showing different rate performances of the sodium ion battery prepared in Example 5 in the voltage range of 2-4.7 V;
[0040] Fig. 9 This is the XRD pattern of the sodium ion battery positive electrode material prepared in Example 2;
[0041] Fig.10 This is a SEM image of the sodium ion battery positive electrode material prepared in Example 2;
[0042] Fig.11 The charge and discharge curve of the sodium ion battery prepared in Example 6 at a voltage range of 2-4.7V and a current density of 0.2C;
[0043] Fig.12The charge and discharge curve of the sodium ion battery prepared in Example 6 at a voltage range of 2-4.5V and a current density of 0.2C;
[0044] Fig.13 This is a cycle performance diagram of the sodium ion battery prepared in Example 6 at a current density of 1C;
[0045] Fig.14 This is a performance diagram of different rates of the sodium ion battery prepared in Example 6 in the voltage range of 2-4.5V;
[0046] Fig.15 This is the XRD pattern of the sodium ion battery positive electrode material prepared in Example 3;
[0047] Fig.16 This is a SEM image of the sodium ion battery positive electrode material prepared in Example 3;
[0048] Fig.17 The charge and discharge curve of the sodium ion battery prepared in Example 7 at a voltage range of 2-4.5V and a current density of 0.2C;
[0049] Fig.18 This is a cycle performance diagram of the sodium ion battery prepared in Example 7 at a voltage range of 2-4.5V and a current density of 1C;
[0050] Fig.19 This is the XRD pattern of the sodium ion battery positive electrode material prepared in Example 4;
[0051] Fig. 20 This is a SEM image of the sodium ion battery positive electrode material prepared in Example 4;
[0052] Fig.21 The charge and discharge curve of the sodium ion battery prepared in Example 8 at a voltage range of 2-4.5V and a current density of 0.2C;
[0053] Fig. 22 This is a cycle performance diagram of the sodium ion battery prepared in Example 8 at a voltage range of 2-4.5V and a current density of 1C;
[0054] Fig.23 This is a cycle performance diagram of the sodium ion battery prepared in Example 8 at a voltage range of 2-4.7V and a current density of 1C;
[0055] Fig.24 This is the XRD pattern of the sodium ion battery positive electrode material prepared in Comparative Example 1;
[0056] Fig.25 This is a SEM image of the sodium ion battery positive electrode material prepared in Comparative Example 1;
[0057] Fig.26The charge and discharge curve of the sodium ion battery prepared in Comparative Example 3 at a voltage range of 2-4.5V and a current density of 0.2C;
[0058] Fig. 27 The charge and discharge curve of the sodium ion battery prepared in Comparative Example 3 at a voltage range of 2-4.7V and a current density of 0.2C;
[0059] Fig.28 This is a cycle performance diagram of the sodium ion battery prepared in Comparative Example 3 in the voltage range of 2-4.5V and at a current density of 1C;
[0060] Fig.29 This is a cycle performance diagram of the sodium ion battery prepared in Comparative Example 3 in the voltage range of 2-4.7V and at a current density of 1C;
[0061] Fig.30 This is the XRD pattern of the sodium ion battery positive electrode material prepared in Comparative Example 2;
[0062] Fig.31 This is a SEM image of the sodium ion battery positive electrode material prepared in Comparative Example 2;
[0063] Fig.32 The charge and discharge curve of the sodium ion battery prepared in Comparative Example 4 at a voltage range of 2-4.5V and a current density of 0.2C;
[0064] Fig.33 This is a cycling performance diagram of the sodium ion battery prepared in Comparative Example 4 in the voltage range of 2-4.5V and a current density of 1C. DETAILED DESCRIPTION
[0065] The technical solution of the present invention is further described below in conjunction with specific embodiments.
[0066] The raw material information involved in the following examples is as follows:
[0067] The sodium source (sodium carbonate) was purchased from Fuchen (Tianjin) Chemical Reagent Co., Ltd., and the copper source (CuO), iron source (Fe2O3), nickel source (NiO), manganese source (Mn2O3) and lithium source (Li2CO3) were purchased from McLean Reagent.
[0068] The various performance indicators in the following examples are strictly measured using precise instruments or standard test methods:
[0069] The crystal structure (XRD pattern) of the samples was determined by X-ray diffractometer (ARL EQUINOX 3000, Thermo Fisher Scientific) at 40 kV and 40 mA with a 2θ range of 10 to 80°.
[0070] The microstructure was observed using a scanning electron microscope (SEM, Quanta FEG, USA).
[0071] 7 Liss-NMR: performed on an Agilent 600DD2 spectrometer (magnetic field strength 14.1T, Agilent, USA). 7 The Larmor frequency of Li proton decoupling (TPPM) during the acquisition process was 233.08 MHz. The powder sample was placed in a 4.0 mm pencil zirconia rotor with a cycle delay of 3 s. The spectrum was acquired at a rotation speed of 8 kHz, a pulse width of 90 degrees (3.8 us), and 128 scans. The Li signal of LiCl was used as 7 The powder sample is one of the positive electrode materials for sodium ion batteries prepared in Examples 1 to 4 and Comparative Examples 1 to 2.
[0072] The charge and discharge performance test of sodium ion battery is carried out on the CT type produced by Wuhan Shenglan Electronic Technology Co., Ltd.
[0073] The test was carried out on the 2001A Blue Electric test system.
[0074] The sodium ion battery positive electrode material of the present invention is a sodium ion battery positive electrode material that is stably cycled at high voltage by Li double-site doping. The doped Li element stabilizes the transition metal layer lattice; the doped Ni element can inhibit Fe 3+ The Cu element can enhance the air stability of the material, and the strong Cu-O covalency can inhibit the over-oxidation of oxygen by forming a stable Cu-(OO) interaction. Therefore, the lattice oxygen loss and irreversible TM migration are simultaneously suppressed.
[0075] Embodiments 1 to 4
[0076] A method for preparing a positive electrode material for a sodium ion battery comprises the following steps:
[0077] S1, mixing a sodium source, a copper source, an iron source, a manganese source, a nickel source and a lithium source, placing the mixture in an alumina ball mill, and wet-milling the mixture until uniform (using acetone as a wet-milling dispersant) to obtain a precursor powder, wherein the ratio of sodium in the sodium source, copper in the copper source, iron in the iron source, nickel in the nickel source, manganese in the manganese source and lithium in the lithium source is X, and the value of X is shown in Table 1, the sodium source is sodium carbonate, the copper source is copper oxide (CuO), the iron source is iron oxide (Fe2O3), the manganese source is manganese oxide (Mn2O3), the nickel source is nickel oxide (NiO), and the lithium source is lithium carbonate (Li2CO3), the rotation speed of the wet-milling is 1400 rpm, and the time of the wet-milling is 2 h;
[0078] S2, placing the precursor powder in a muffle furnace, heating it to 900° C. at a heating rate of 5° C. / min in an air atmosphere, and sintering it at 900° C. for 12 hours to obtain a positive electrode material for a sodium ion battery.
[0079] Table 1
[0080]
[0081] Comparative Example 1
[0082] A sodium ion battery positive electrode material (Na 0.7 [Cu 0.2 Fe 0.1 Ni 0.1 Mn 0.6 ]O2) preparation method, comprising the following steps:
[0083] S1, mixing a sodium source, a copper source, an iron source, a manganese source and a nickel source, placing the mixture in an alumina ball mill, and wet-milling the mixture until uniform (using acetone as a wet-milling dispersant) to obtain a precursor powder, wherein the ratio of sodium in the sodium source, copper in the copper source, iron in the iron source, manganese in the manganese source and nickel in the nickel source is 0.735:0.2:0.1:0.6:0.1, the sodium source is sodium carbonate, the copper source is copper oxide (CuO), the iron source is iron oxide (Fe2O3), the manganese source is manganese oxide (Mn2O3), the nickel source is nickel oxide (NiO), the rotation speed of the wet-milling is 1400 rpm, and the time of the wet-milling is 2 h;
[0084] S2, placing the precursor powder in a muffle furnace, heating it to 900° C. at a heating rate of 5° C. / min in an air atmosphere, and sintering it at 900° C. for 12 hours to obtain a positive electrode material for a sodium ion battery.
[0085] Comparative Example 2
[0086] A sodium ion battery positive electrode material (Na 0.7 [Cu 0.2 Fe 0.2 Mn 0.52 Li 0.08 ]O2) preparation method, comprising the following steps:
[0087] S1, mixing a sodium source, a copper source, an iron source, a manganese source and a lithium source, placing the mixture in an alumina ball mill, and wet-milling the mixture until uniform (using acetone as a wet-milling dispersant) to obtain a precursor powder, wherein the ratio of sodium in the sodium source, copper in the copper source, iron in the iron source, manganese in the manganese source and lithium in the lithium source is 0.735:0.2:0.2:0.52:0.084 in terms of the amount of substance, the sodium source is sodium carbonate, the copper source is copper oxide (CuO), the iron source is iron oxide (Fe2O3), the manganese source is manganese oxide (Mn2O3), the lithium source is lithium carbonate, the rotation speed of the wet-milling is 1400 rpm, and the time of the wet-milling is 2 h;
[0088] S2, placing the precursor powder in a muffle furnace, heating it to 900° C. at a heating rate of 5° C. / min in an air atmosphere, and sintering it at 900° C. for 12 hours to obtain a positive electrode material for a sodium ion battery.
[0089] Examples 5 to 8 and Comparative Examples 3 to 4
[0090] A sodium ion battery comprises: a positive electrode sheet, an electrolyte, a diaphragm and a negative electrode sheet, wherein the preparation method comprises: assembling the positive electrode shell, the positive electrode sheet, the diaphragm, the negative electrode sheet, the gasket, the spring sheet and the negative electrode shell in the order of the positive electrode shell, to obtain the sodium ion battery, wherein the electrolyte used is a NaClO4 type high-voltage electrolyte, the electrolyte in the electrolyte is NaClO4, and the concentration of the electrolyte in the electrolyte is 1 mol L -1 The solvents in the electrolyte are propylene carbonate (PC) and fluoroethylene carbonate (FEC), and the ratio of propylene carbonate to fluoroethylene carbonate is 95:5 by volume. The negative electrode sheet is a sodium sheet, and the separator is a glass fiber. The method for obtaining the positive electrode sheet is as follows: the positive electrode material, the conductive agent (acetylene black) and the binder solution are mixed and ground to be uniform to obtain a slurry, the slurry is uniformly coated on an aluminum foil, and dried in a vacuum oven at 80°C for 12 hours, and cut into circular electrode sheets with a diameter of 12 mm using a sheet cutter (the loading amount of the positive electrode material on the circular electrode sheet with a diameter of 12 mm is 1.5 mg), and then the circular electrode sheet is pressed at a pressure of 10 MPa for 30 seconds using a sheet press to obtain a positive electrode sheet, wherein the binder solution is a mixture of polyvinylidene fluoride (PVDF, powder) and N-methylpyrrolidone, and the concentration of polyvinylidene fluoride (PVDF) in the binder solution is 20 mg ml -1 , by mass, the ratio of the positive electrode material, the conductive agent and the PVDF in the binder solution is 8:1:1. The positive electrode material is one of the positive electrode materials for sodium ion batteries prepared in Examples 1 to 4 and Comparative Examples 1 to 2.
[0091] Table 2
[0092] Sodium-ion batteries Preparation of positive electrode materials for sodium ion batteries Example 5 Example 1 Example 6 Example 2 Example 7 Example 3 Example 8 Example 4 Comparative Example 3 Comparative Example 1 Comparative Example 4 Comparative Example 2
[0093] Example 1 The XRD pattern of the sodium ion battery cathode material prepared Figure 1 As shown, Figure 1 XRD patterns and P2-type layered Na 0.7 MnO 2.05 (P63 / mmc, JCPDS NO.27-0751), O3-type layered NaNi 0.5 Mn 0.5 O2 (JCPDS NO.54-0887), the sodium ion battery positive electrode material prepared in Example 1 has a P2 / O3 dual-phase structure.
[0094] Example 1 SEM of the prepared sodium ion battery positive electrode material Figure 2 As shown, through SEM observation, the sodium ion battery positive electrode material prepared in Example 1 is a layered structure.
[0095] Example 1 Preparation of the obtained sodium ion battery positive electrode material 7 Li ss-NMR Figure 3 As shown, 7 Li ss-NMR analysis shows that the Li element in the sodium ion battery positive electrode material prepared in Example 1 is double-doped, where Li accounts for 37.5% (Li AM :37.5%), Li accounts for 62.5% in the transition metal layer (Li TM :62.5%).
[0096] The charge and discharge curve of the sodium ion battery prepared in Example 5 in the voltage range of 2-4.7V is as follows Figure 4 As shown, after analysis, the sodium ion battery prepared in Example 5 has a current density of 177 mAh g -1 The discharge specific capacity and the first-cycle coulomb efficiency are 83%.
[0097] The charge and discharge curve of the sodium ion battery prepared in Example 5 in the voltage range of 2-4.5V is as follows Figure 5 As shown, after analysis, the sodium ion battery prepared in Example 5 has a current density of 172 mAh g -1 The discharge specific capacity and the first-cycle coulomb efficiency are 93%.
[0098] Example 5 The cycle performance of the sodium ion battery prepared at 1C current density is as follows Figure 6 As shown, in the voltage range of 2-4.5V, the initial discharge capacity is 146mAh g -1 After 100 cycles, the capacity is 144 mAh g -1The capacity retention rate of the sodium ion battery prepared in Example 5 after 100 cycles is 98.6%. In the voltage range of 2-4.7V, the initial discharge specific capacity is 149mAh g -1 After 100 cycles, the capacity is 133 mAh g -1 The capacity retention rate of the sodium ion battery prepared in Example 5 after 100 cycles is 89%.
[0099] Example 5 The cycle performance of the sodium ion battery prepared at a current density of 2C is as follows Figure 7 As shown, in the voltage range of 2-4.5V, the initial discharge capacity is 127mAh g -1 After 200 cycles, the capacity is 108 mAh g -1 The capacity retention rate of the sodium ion battery prepared in Example 5 after 200 cycles is 85%. In the voltage range of 2-4.7V, the initial discharge specific capacity is 142mAhg -1 After 200 cycles, the capacity is 113 mAh g -1 The capacity retention rate of the prepared sodium ion battery after 200 cycles was 79.6%.
[0100] The rate performance of the sodium ion battery prepared in Example 5 is shown in Figures 8(a) and 8(b). In the voltage range of 2-4.5V, 0.1C, 0.2C, 0.5C, 1C, 2C, 5C and 10C, the discharge specific capacity has a downward trend with the increase of current density, and the initial capacity can still be reached when the current density returns to 0.1C. In the voltage range of 2-4.7V, 0.2C, 0.5C, 1C, 2C, 5C and 10C, the discharge specific capacity has a downward trend with the increase of current density, and the initial capacity can still be reached when the current density returns to 0.2C, which proves that the sodium ion battery has strong reversibility.
[0101] Example 2 The XRD pattern of the sodium ion battery cathode material prepared Fig. 9 As shown, Fig. 9 XRD patterns and P2-type layered Na 0.7 MnO 2.05 (P63 / mmc, JCPDS NO.27-0751), O3-type layered NaNi 0.5 Mn 0.5 O2 (JCPDS NO.54-0887), the sodium ion battery positive electrode material prepared in Example 2 has a P2 / O3 dual-phase structure.
[0102] Example 2 SEM of the prepared sodium ion battery positive electrode material Fig.10 As shown, through SEM observation, the sodium ion battery positive electrode material prepared in Example 2 is a layered structure.
[0103] The charge and discharge curve of the sodium ion battery prepared in Example 6 in the voltage range of 2-4.7V is as follows Fig.11 As shown, after analysis, the sodium ion battery prepared in Example 6 has a current density of 154 mA hg at 0.2C. -1 The discharge specific capacity and the first-cycle coulomb efficiency are 90.4%.
[0104] The charge and discharge curve of the sodium ion battery prepared in Example 6 in the voltage range of 2-4.5V is as follows Fig.12 As shown, after analysis, the sodium ion battery prepared in Example 6 has a current density of 145 mA hg at 0.2C. -1 The discharge specific capacity and the first-cycle coulomb efficiency are 97.5%.
[0105] Example 6 The cycle performance of the sodium ion battery prepared at 1C current density is as follows Fig.13 As shown, in the voltage range of 2-4.5V, the initial discharge capacity is 138mAh g -1 After 100 cycles, the capacity is 124 mAh g -1 The capacity retention rate of the sodium ion battery prepared in Example 6 after 100 cycles was 89.8%. In the voltage range of 2-4.7V, the initial discharge specific capacity was 135mAh g -1 After 80 cycles, the capacity is 119 mAh g -1 The capacity retention rate of the sodium ion battery prepared in Example 6 after 80 cycles is 88%.
[0106] Example 6 The rate performance of the sodium ion battery prepared in the voltage range of 2-4.5V is as follows Fig.14 As shown, although the discharge specific capacity tends to decrease with the increase of current density at 0.2C, 0.5C, 1C, 2C, 5C and 10C, the initial capacity can still be reached when the current density returns to 0.2C, which proves that the sodium ion battery prepared in Example 6 has strong reversibility.
[0107] Example 3 The XRD pattern of the sodium ion battery cathode material prepared Fig.15 As shown, Fig.15 XRD patterns and O3-type layered NaNi 0.5 Mn 0.5 O2 (JCPDS NO.54-0887), the positive electrode material of the sodium ion battery prepared in Example 3 is an O3 phase structure. The O3 phase structure alone is difficult to achieve both coulombic efficiency and cycle stability.
[0108] Example 3 SEM of the prepared sodium ion battery positive electrode material Fig.16As shown, through SEM observation, the sodium ion battery positive electrode material prepared in Example 3 is a layered structure.
[0109] The charge and discharge curve of the sodium ion battery prepared in Example 7 in the voltage range of 2-4.5V is as follows Fig.17 As shown, after analysis, the sodium ion battery prepared in Example 7 has a current density of 145 mA hg at 0.2C. -1 The discharge specific capacity and the first-cycle coulomb efficiency are 89.7%.
[0110] Example 7 The cycle performance of the sodium ion battery prepared at 1C current density is as follows Fig.18 As shown, in the voltage range of 2-4.5V, the initial discharge capacity is 128mAh g -1 After 100 cycles, the capacity is 127 mAh g -1 The capacity retention rate of the sodium ion battery prepared in Example 7 after 100 cycles is 99%.
[0111] Example 4 The XRD pattern of the sodium ion battery cathode material prepared Fig.19 As shown, Fig.19 XRD patterns and P2-type layered Na 0.7 MnO 2.05 (P63 / mmc, JCPDS NO.27-0751), O3-type layered NaNi 0.5 Mn 0.5 O2 (JCPDS NO.54-0887) matches, and the sodium ion battery positive electrode material prepared in Example 4 has a P2 / O3 dual-phase structure.
[0112] Example 4 SEM of the prepared sodium ion battery positive electrode material Fig. 20 As shown, through SEM observation, the sodium ion battery positive electrode material prepared in Example 4 has a layered structure.
[0113] The charge and discharge curve of the sodium ion battery prepared in Example 8 in the voltage range of 2-4.5V is as follows Fig.21 As shown, after analysis, the sodium ion battery prepared in Example 8 has a current density of 143 mA hg at 0.2C. -1 The discharge specific capacity and the first-cycle coulomb efficiency are 99.7%.
[0114] The cycle performance of the sodium ion battery prepared in Example 8 at a current density of 1C is as follows Fig. 22 As shown, in the voltage range of 2-4.5V, the initial discharge capacity is 130mAh g -1 After 100 cycles, the capacity is 119 mAh g -1The capacity retention rate of the sodium ion battery prepared in Example 8 after 100 cycles is 91.6%.
[0115] The cycle performance of the sodium ion battery prepared in Example 8 at a current density of 1C is as follows Fig.23 As shown, in the voltage range of 2-4.7 V, the initial discharge capacity is 127 mAh g -1 After 100 cycles, the capacity is 118 mAh g -1 The capacity retention rate of the sodium ion battery prepared in Example 8 after 100 cycles is 93%.
[0116] The XRD pattern of the sodium ion battery positive electrode material prepared in Comparative Example 1 is as follows: Fig.24 As shown, Fig.24 XRD patterns and P2-type layered Na 0.7 MnO 2.05 (P63 / mmc, JCPDS NO.27-0751), the sodium ion battery positive electrode material prepared in Comparative Example 1 is a P2 single-phase structure.
[0117] Comparative Example 1: SEM of the sodium ion battery positive electrode material prepared Fig.25 As shown, through SEM observation, the sodium ion battery positive electrode material prepared in Comparative Example 1 has a layered structure, but the grains are smaller than those in the examples.
[0118] The charge and discharge curve of the sodium ion battery prepared in Comparative Example 3 in the voltage range of 2-4.5V is as follows Fig.26 As shown, after analysis, the sodium ion battery prepared in Comparative Example 3 has a current density of 140 mA hg -1 The discharge specific capacity and the first-cycle coulomb efficiency are 117%.
[0119] The charge and discharge curve of the sodium ion battery prepared in Comparative Example 3 in the voltage range of 2-4.7V is as follows Fig. 27 As shown, after analysis, the sodium ion battery prepared in Comparative Example 3 has a current density of 145 mAh g -1 The discharge specific capacity and the first-cycle coulomb efficiency are 112.6%.
[0120] The cycle performance of the sodium ion battery prepared in Comparative Example 3 at a current density of 1C is as follows: Fig.28 As shown, it has 118.9mA hg at 2-4.5V voltage range -1 The initial discharge capacity is 77.6 mA hg after 100 cycles. -1 , the capacity retention rate is 65.3%.
[0121] The cycle performance of the sodium ion battery prepared in Comparative Example 3 at a current density of 1C is as follows: Fig.29 As shown, it has 129.3mA hg at 2-4.7V voltage range -1 The initial discharge capacity is 88 mA hg after 100 cycles. -1 , the capacity retention rate is 68%.
[0122] The XRD pattern of the sodium ion battery positive electrode material prepared in Comparative Example 2 is as follows: Fig.30 As shown, Fig.30 XRD patterns and O3-type layered NaNi 0.5 Mn 0.5 O2 (JCPDS NO.54-0887) matches, and the sodium ion battery positive electrode material prepared in Comparative Example 2 is an O3 single-phase structure.
[0123] Comparative Example 2 SEM of the sodium ion battery positive electrode material prepared Fig.31 As shown, through SEM observation, the sodium ion battery positive electrode material prepared in Comparative Example 2 has a layered structure and relatively large grains.
[0124] The charge and discharge curve of the sodium ion battery prepared in Comparative Example 4 in the voltage range of 2-4.5V is as follows Fig.32 As shown, after analysis, the sodium ion battery prepared in Comparative Example 4 has a current density of 170 mA hg -1 The discharge specific capacity and the first-cycle coulomb efficiency are 102.7%.
[0125] Comparative Example 4 The cycle performance of the sodium ion battery prepared at 1C current density is as follows Fig.33 As shown, it has 128mA hg at 2-4.5V voltage range -1 The initial discharge capacity is 123 mA hg after 69 cycles. -1 , the capacity retention rate is 96%.
[0126] The electrochemical properties of the sodium ion batteries of Examples 5 to 8 and Comparative Examples 3 to 4 are shown in Tables 3 and 4. In the electrochemical test, the discharge specific capacity of the sodium ion batteries prepared in Examples 5 to 8 is higher than that of the comparative example, and the cycle stability is also higher than that of the comparative example. This is because the sodium ion battery positive electrode material prepared in Examples 1 to 4 effectively suppresses lattice distortion and element mixing during the charge and discharge process through the action of the Li element.
[0127] Table 3 (Discharge specific capacity, first cycle coulombic efficiency and cycle stability of the sodium ion batteries of Examples 5 to 8 and Comparative Example 3 at 2-4.7V)
[0128]
[0129] Table 4 (Discharge specific capacity, first cycle coulomb efficiency and cycle stability of sodium ion batteries of Examples 5 to 8 and Comparative Examples 3 to 4 at 2-4.5V)
[0130]
[0131] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.
Claims
1. A sodium ion battery positive electrode material, characterized in that: Its general structural formula is [Na 0.7 Li 0.03 [Cu x Fe y Ni z Mn 0.92-x-y-z Li 0.05 O₂, where 0.1 ≤ x ≤ 0.4, 0.1 ≤ y ≤ 0.3, 0.1 ≤ z ≤ 0.3, 0.1 ≤ 0.92 - x - y - z ≤ 0.
6.
2. The sodium ion battery positive electrode material according to claim 1, characterized in that 0.1≤x≤0.2, 0.1≤y≤0.14, 0.1≤z≤0.3, 0.3≤0.92-xyz≤0.
6.
3. The method for preparing a positive electrode material for a sodium ion battery according to any one of claims 1 to 2, characterized in that: The following steps are involved: S1, mixing a sodium source, a copper source, an iron source, a manganese source, a nickel source and a lithium source uniformly to obtain a precursor powder, wherein the ratio of sodium in the sodium source, copper in the copper source, iron in the iron source, nickel in the nickel source, manganese in the manganese source and lithium in the lithium source is 0.735:x:y:z:(0.92-xyz):0.084 in terms of molar fractions; S2, sintering the precursor powder at 500-950° C. for 10-15 hours to obtain a positive electrode material for a sodium ion battery.
4. The preparation method according to claim 3, characterized in that: In S1, a sodium source, a copper source, an iron source, a manganese source, a nickel source and a lithium source are mixed and wet-ball-milled to be uniform.
5. A sodium ion battery positive electrode material, characterized in that: Its structural formula is Na 0.7 [Cu 0.2 Fe 0.2 Mn 0.52 Li 0.08 ]O2.
6. The method for preparing a positive electrode material for a sodium ion battery according to claim 5, characterized in that: The following steps are involved: S1, mixing a sodium source, a copper source, an iron source, a manganese source and a lithium source uniformly to obtain a precursor powder, wherein the ratio of sodium in the sodium source, copper in the copper source, iron in the iron source, manganese in the manganese source and lithium in the lithium source is 0.735:0.2:0.2:0.52:0.084 in terms of molar fractions; S2, sintering the precursor powder at 500-950° C. for 10-15 hours to obtain a positive electrode material for a sodium ion battery.
7. A sodium ion battery, characterized in that: include: A positive electrode, a negative electrode and a separator, wherein the positive electrode material in the positive electrode is the positive electrode material for a sodium ion battery as described in claim 1.
8. The sodium ion battery according to claim 7, characterized in that: The sodium ion battery has a cycle stability of up to 98.6% after 100 cycles at a high voltage of 2-4.5V and a current density of 1C.
9. The sodium ion battery according to claim 7, characterized in that: The sodium ion battery has a cycle stability of up to 89% after 100 cycles at a high voltage of 2-4.7V and a current density of 1C.
10. Use of the sodium ion battery positive electrode material as claimed in claim 1 in a sodium ion battery, wherein the sodium ion battery can still have high specific capacity, excellent cycle stability and excellent rate performance when operating at a high voltage of 2.0-4.7V.
Citation Information
Cited By
O3-P2 layered double-phase sodium ion battery positive electrode material and preparation method thereof
CN120784353A